2017
DOI: 10.4274/cayd.52523
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carbon Monoxide Poisoning on Platelet Volume in Children

Abstract: GirişKarbonmonoksit (CO), karbon içeren maddelerin tam yanmaması sonucu oluşan, renksiz, kokusuz, tatsız, irritan olmayan ve toksik bir gazdır. Özellikle kış aylarında sıklığı artan CO zehirlenmeleri, ülkemizde ve dünyada önemli bir toplum sağlığı sorunudur. Çocukluk çağında görülen zehirlenmeler arasında CO zehirlenmesi genellikle ilk üç sırada yer alır.1 CO zehirlenmesi önemli bir morbidite ve mortalite nedenidir. Birçok organ sistemi tutulabilir ve fark edilmeyen maruziyetler ölümle sonuçlanabilir. Ülkemizd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Marchewka et al 49 reported that MPV was significantly negatively correlated with disease severity in COP. Akça et al and Bağcı et al 19,40 found no statistically significant difference between the severe COP group and mild to moderate COP group in terms of platelet count and MPV. According to previous research, the platelet count was statistically significantly higher in the severe group than in the control group in our study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Marchewka et al 49 reported that MPV was significantly negatively correlated with disease severity in COP. Akça et al and Bağcı et al 19,40 found no statistically significant difference between the severe COP group and mild to moderate COP group in terms of platelet count and MPV. According to previous research, the platelet count was statistically significantly higher in the severe group than in the control group in our study.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, free oxygen radicals produced by COP may promote platelet adhesion and aggregation. 19 According to Coşkun et al, 38 MPV levels were significantly higher in patients with CO intoxication. 18 Karabacak et al 47 discovered a high prevalence of COP and platelet count in adults, as well as the possibility that MPV could be a useful diagnostic tool for predicting prognosis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…CO as toxic gas causes mortal poisoning. CO and NOx emissions of USA in 2017 are reported as 60109 and 10776 in thousands of tons [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%